2021
DOI: 10.1111/rec.13548
|View full text |Cite
|
Sign up to set email alerts
|

Control of invasive Phragmites australis (European common reed) alters macroinvertebrate communities

Abstract: Wetland restoration often involves invasive‐plant suppression to encourage the recovery of native‐dominated vegetation communities. However, assessment of recovery is usually focused only on vegetation, and the response of other critical wetland biota, such as macroinvertebrates, is seldom assessed. We characterized the aquatic, semi‐aquatic, and terrestrial macroinvertebrate communities in remnant, uninvaded marsh to identify restoration targets and compared this to the communities in Phragmites australis‐inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ensuring an ecosystem is balanced in the various aspects examined throughout this paper is an effective strategy in preserving biological communities for the future (Rahel & Olden, 2008). Many published studies have reported overall ecosystem improvement upon Phragmites removal, as well as identified correlations between invasions and decreased ecosystem capacity to buffer other disturbance effects, such as extreme weather influenced by climate change (Rahel & Olden, 2008;Tozer & Mackenzie, 2019;Robichaud et al, 2021;Modzer & Zieman, 2010;Meyerson et al,1999;Borin et al, 2011;Lenters et al, 2011;Bergquist et al, 2007). Other literature has also supported Phragmites invasions within the Great Lakes wetlands to be amplified by climate change.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ensuring an ecosystem is balanced in the various aspects examined throughout this paper is an effective strategy in preserving biological communities for the future (Rahel & Olden, 2008). Many published studies have reported overall ecosystem improvement upon Phragmites removal, as well as identified correlations between invasions and decreased ecosystem capacity to buffer other disturbance effects, such as extreme weather influenced by climate change (Rahel & Olden, 2008;Tozer & Mackenzie, 2019;Robichaud et al, 2021;Modzer & Zieman, 2010;Meyerson et al,1999;Borin et al, 2011;Lenters et al, 2011;Bergquist et al, 2007). Other literature has also supported Phragmites invasions within the Great Lakes wetlands to be amplified by climate change.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, an investigation monitoring the differences in aquatic, semi-aquatic, and terrestrial invertebrate community compositions showed little distinction between Phragmitesinvaded and uninvaded marshes, suggesting that Phragmites has little affect on macroinvertebrate communities (Robichaud et al, 2021). However, in sites where herbicide was applied for control of Phragmites, aquatic and semi-aquatic invertebrate community composition shifted, as Chironomidae, Leptoceridae, and Caenidae became the dominating invertebrate taxa in the community (Robichaud et al, 2021).…”
Section: Species Diversity Richness and Composition Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in northeast England and Washington restored the bare surfaces of silt and sand in areas cleared of Common Cordgrass ( Spartina anglica ) by using herbicide, turning the areas into a habitat suitable for benthic organisms and attracting waterbirds to re‐use these wetlands (Evans 1986; Patten & O'Casey 2007). Therefore, comparing the density and biomass of benthic organisms between S. alterniflora eradicated areas and bare tidal flat areas (where S. alterniflora was absent) can improve our understanding of the effects of S. alterniflora eradication on benthic communities, and it may explain the distribution of waterbirds across these habitats (Robichaud et al 2022).…”
Section: Introductionmentioning
confidence: 99%